Fiqh al-Bī’ah and Mining Concessions: NU and Muhammadiyah’s Legal Responses - Sudarmin, Andi B. Mutmainnah; Amri, Ulil; Amelia, Riska; Rismawati, Rismawati; Ajmalunnas M (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2025)
This study examines the responses of Nahdlatul Ulama (NU) and Muhammadiyah to Government Regulation Number 25 of 2024, which grants mining concession permits to Islamic community organizations, by employing the perspective of fiqh al-bī’ah (Islamic environmental jurisprudence). Using a descriptive qualitative method with a literature-based approach, the research analyzes primary data in the form of official statements and fatwas issued by NU and Muhammadiyah, as well as secondary data from academic literature, policy documents, and studies on mining governance and environmental ethics. The findings reveal that both organizations accept the mining concession policy conditionally, emphasizing the readiness of human resources, institutional capacity, and a strong commitment to environmental protection as fundamental requirements. Their responses consistently underline that mining activities must adhere to the principles of fiqh al-bī’ah, particularly environmental stewardship, social justice, and the pursuit of public welfare (maṣlaḥah). The originality of this study lies in its integration of Islamic environmental jurisprudence with public policy analysis to assess the role of religious mass organizations in extractive industry governance. The study implies that Islamic organizations can function as moral and ethical agents in promoting environmentally responsible mining practices, while also highlighting the importance of embedding Islamic environmental values within natural resource management policies in Indonesia.